(untitled) (Research, Society and Development, 2022)
The aim of the study was to compare, through critical and interpretive analysis, the past of the Spanish flu epidemic crisis and the present of the Covid-19 pandemic crisis in Brazil. For this purpose, the dialectical scientific method was applied through an integrative literature review, examining data collected from Google Scholar, PubMed and Lilacs databases. As a result, it was observed that the spread of diseases in both pandemics studied was due to social and governmental denialism that favored the lack of containment measures and, consequently, the overload of systems, reflecting on the number of cases of the disease that caused several deaths at a high level, both reflected in consequences in communities with little infrastructure and lack of access to inadequate urban sanitation, in both there was the use of masks, washing of hands and also social distancing, as well as the great amount of fake news spread by the community. It is concluded that there are similarities between the past and the present regarding the causes and consequences of pandemics, and it is important to analyze and compare the factors and historical, social and economic concepts present in the various conjunctures of population health.